Pengaruh Pola Asuh Orang Tua terhadap Kepribadian Anak di RA Ayatun Najihin NW Gawah Gadung: The Influence of Parenting Styles on Children's Personalities at RA Ayatun Najihin NW Gawah Gadung - Yuliana Susanti; Husni Zakiah (Pendidikan Al-Gafari, 2025)
Parental care is very important for children and will affect the child's life until he is an adult. Therefore, parents should pay attention to choosing the right parenting style so that children have a good personality. This study aims: 1) To find out the parenting style applied by parents. 2) To find out the influence of parenting style on children's personalities and children's personalities. This study is a qualitative study with a qualitative descriptive approach, namely presentation in written form and explaining as it is according to the actual situation in the field. The results of this study indicate that the types of parenting styles applied by parents at RA Ayatun Najihin NW Gawah Gadung are Democratic parenting and Permissive parenting. The influence of Democratic parenting on children's personalities is that it can form good children's personalities including discipline, sociability, likes to share, respects friends and is responsible. While Permissive parenting can form bad children's personalities, for example, children like to disturb friends, are difficult to manage, want to win alone, are irresponsible, and lack discipline. Meanwhile, the personalities of the children at RA Ayatun Najihin NW Gawah Gadung, which totals 34 children, 30 of them already have good personalities, but 4 of them do not have good personalities.